Metal-carbon / rubber based on MOFs derivation as well as preparation method and application of metal-carbon / rubber
Through the metal @carbon/rubber preparation method derived based on MOFs, the problems of uneven particle dispersion and complex process of metal @carbon composite materials during the carbon thermal reduction process are solved, and efficient electromagnetic wave absorption and simplified process flow are achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411983510.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
During the carbon-thermal reduction process, the metal particles have large differences in the particle sizes and are unevenly dispersed, which affects the absorption performance. The process flow is complex and the carbon content is small, which is not conducive to industrial production.
Using the preparation method of metal @carbon/rubber derived based on MOFs, a jelly-like precursor is formed by reacting bisaccharide derivatives, metal salts and polyacrylonitrile in a solvent to form a jelly-like precursor. After drying and phased carbonization, MOFs-derived metal @carbon composite material is obtained, and it is combined with rubber and additives through rubber refining and vulcanization processing.
The uniform dispersion and particle size regulation of metal particles are achieved, the electromagnetic wave absorption characteristics of wave absorbing materials are improved, the process flow is simplified, the output of carbon materials is improved, and it is suitable for industrial production.
Smart Images

Figure CN119751992A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical materials and relates to the improvement of metal@carbon materials. Background Art
[0002] The electromagnetic radiation generated by modern electronic devices when they are working not only seriously endangers human health, but also may cause electromagnetic wave cross-interference between electronic components of different frequencies in electronic devices, causing electromagnetic compatibility problems and damage to sensitive devices. At present, carbon material composite metal particles are widely used in electromagnetic wave absorption materials due to their excellent physical and chemical properties. At present, carbon thermal reduction technology is usually used to prepare metal@carbon composite materials. However, during the research process, it was found that the nucleation and growth of metals in carbon thermal reduction cannot be effectively controlled, resulting in large differences in particle size and uneven dispersion of metal particles in carbon nanofibers during carbon thermal reduction, affecting the overall wave absorption performance of metal@carbon.
[0003] To solve the above problems, the spatial confinement effect is generally used to hinder the diffusion and growth of metal atoms. For example, the metal-MOFs structure is constructed to achieve the refinement and uniform distribution of metal particles. At present, such materials are widely studied in the fields of catalysis and electrochemistry, such as Ni single-atom catalysts. Since the addition of polymers (such as PAN, PVP, etc.) to the solution system for preparing Ni-MOFs will affect the formation of Ni-MOFs. Therefore, this method mostly uses Ni ions and organic ligands (terephthalic acid, etc.) to mix, and then form a Ni-MOFs structure through solvent thermal, hydrothermal reaction or reflux method, and then form a Ni / C composite material through high-temperature carbonization. The problem with this method is that the process flow is complicated and the carbon content is small, which means that the output of carbon materials is low, which is not conducive to industrial production and application. (CN107216854A, CN109304476A, CN107267124A are similar in ideas) With the development of society, power electronic equipment is constantly developing towards large capacity, high integration, and high power density, while the appearance of the equipment is gradually developing towards miniaturization and lightweight. This will cause the heat generated by power electronic devices to accumulate rapidly and cannot be effectively discharged, which seriously affects the performance and life of electronic components. Therefore, the heat dissipation problem generated by electronic devices and electrical energy equipment during application needs to be solved urgently. Thermal conductive materials are usually used to absorb and dissipate excess heat on equipment components to prevent electronic devices from overheating in a small environment. The internal space of electronic equipment is small, and thermal conductive materials have occupied the gap space on the surface of the device, and absorbing materials cannot be superimposed. Therefore, achieving efficient heat dissipation and absorption of electromagnetic radiation in the limited space of electronic equipment has become a major difficulty that scientific researchers must overcome. In order to meet market requirements and solve this problem, it is very necessary to develop a new generation of thermal conductive and absorbing dual-function composite materials with high thermal conductivity, excellent absorbing ability and easy processing performance. Summary of the invention
[0004] In view of the problem in the prior art that the agglomeration of magnetic doped alloy particles in carbon materials leads to local impedance mismatch and thus weakens the microwave absorption performance, the present invention proposes a metal@carbon / rubber derived from MOFs and a preparation method and application thereof.
[0005] The technical solution of the present invention is achieved in this way: The preparation method of metal@carbon / rubber based on MOFs is as follows: (1) Dissolve the diacid derivative, metal salt and polyacrylonitrile in a solvent, heat and react at 55-63°C for 1-3 hours, and then react at room temperature for 13-20 hours to obtain a jelly-like precursor solution; wherein the mass ratio of the terephthalic acid derivative, the metal salt and the polyacrylonitrile is 1-18:13-30:25-45.
[0006] (2) The precursor solution of step (1) is dried and carbonized at high temperature to obtain a metal@carbon composite material derived from MOFs; wherein the drying temperature is 55-65°C and the time is 12-24h; the high-temperature carbonization adopts staged carbonization, and the heating rate of the first stage is 2-5°C / min, the carbonization temperature is 300-340°C, and the time is 1-2h; the heating rate of the second stage is 2-5°C / min, the carbonization temperature is 650-850°C, and the time is 1-2h.
[0007] (3) preparing MOFs-derived metal@carbon / rubber by rubber mixing and vulcanization process with rubber, additives and the MOFs-derived metal@carbon composite material of step (2); wherein the mass ratio of rubber, antioxidant, stearic acid, zinc oxide / nano zinc oxide, accelerator, vulcanizing agent and MOFs-derived metal@carbon composite material is 100:0.5-1.5:1-3:0.5-1.5:4-6:1-3:20-60.
[0008] Furthermore, in the above step (1), the bis-acid derivative is any one of aminoterephthalic acid, citric acid, dipicolinic acid and terephthalic acid; the metal salt is one or more of iron salt, nickel salt and cobalt salt. The magnetic metal salt can also be combined with zinc salt, copper salt, manganese salt, zirconium salt and the like.
[0009] Since the formation of MOF is only related to metal cations and organic complexes, its formation process is taken as an example of iron salt: Fe 3++ organic ligand (bis acid derivative) → Fe-MOF, so other types of Fe, Co, Ni salts can also produce the same effect. The present application preferably uses the above-mentioned iron salt as any one of ferric acetylacetonate, ferric nitrate, ferric chloride and copper sulfate; the nickel salt as any one of nickel acetylacetonate, nickel nitrate, nickel chloride and nickel sulfate; the cobalt salt as any one of cobalt acetylacetonate, cobalt nitrate, cobalt chloride and cobalt sulfate.
[0010] Preferably, in the above step (3), the rubber is natural rubber or silicone rubber; the additives include one or more of an antioxidant, stearic acid, zinc oxide / nano zinc oxide, an accelerator and a vulcanizing agent; wherein the antioxidant is antioxidant D, the accelerator is accelerator CZ, and the vulcanizing agent is sulfur or dipentadienyl vulcanizing agent.
[0011] The present invention has the following beneficial effects: 1. The present invention provides a simple method for preparing a MOF-derived metal@carbon composite material with uniformly dispersed doped metal particles and adjustable particle size, which can improve the electromagnetic wave absorption characteristics of the absorbing material and apply it to rubber; the particle size of the MOF-derived metal@carbon composite material prepared in this application is regulated by the MOF structure confinement effect. The existence of the MOF structure allows the metal atoms to be evenly anchored on the carbon fiber on the one hand, and the porous structure of the MOF limits the migration of metal particles during the carbon thermal reduction process on the other hand. Figure 1 It can be seen that the metal particles become uniform and the particle size decreases after the introduction of the MOF structure.
[0012] 2. The present invention prepares a precursor solution containing a metal-MOFs structure by a one-step method, eliminating the need for solvent thermal, hydrothermal or reflux method to prepare the metal-MOFs structure, thereby simplifying the preparation process. Moreover, the C and O elements in the composite material obtained by high-temperature carbonization are evenly distributed, and the Fe nanoparticles of similar size are small, dense, monodispersed and randomly distributed in the carbon matrix; the composite material has a minimum RL of -31.9dB at a thickness of 5.0mm and a frequency of 13.6GHz, and has excellent wave absorption performance; starting from 28°C, the surface temperature of the sample within 120 seconds of heating is statistically calculated. The composite material of the present application can be heated to 55.6°C, while the blank rubber can only be heated to 41.4°C, with high thermal conductivity, suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 These are transmission electron microscopy and energy spectrum characterization images of the Fe@C composite materials of Example 2 and Comparative Example 1; wherein a is a transmission electron microscopy image of Comparative Example 1, b is a transmission electron microscopy image of Example 2, c is a high-resolution transmission image of Example 2, d is a carbon element energy spectrum image of Example 2, e is an oxygen element energy spectrum image of Example 2, and f is an iron element energy spectrum image of Example 2.
[0015] Figure 2 XRD characterization diagram of Co@C composite material; wherein a is the Co@C composite material of Example 5 and Comparative Example 2; b is the Ni@C composite material of Example 5 and Comparative Example 2; c is the FeCoNi@C composite material of Example 11 and Comparative Example 4.
[0016] Figure 3 The wave absorption performance test of the Fe@C composite material of Example 2 and Comparative Example 1; wherein a is the frequency dependence curve of the reflection loss of Comparative Example 1; b is the interference destructive simulation curve of Comparative Example 1; c is the frequency dependence curve of the reflection loss of Example 2; d is the interference destructive simulation curve of Example 2.
[0017] Figure 4 The graphs are thermal conductivity test graphs, wherein a is a graph showing the surface temperature variation of pure silicone rubber, comparative example 4 and example 11 samples heated for 120 seconds, and b is a statistical line graph showing the surface temperature of pure silicone rubber, comparative example 4 and example 11 samples heated for 120 seconds. DETAILED DESCRIPTION
[0018] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Unless otherwise specified, the experimental methods used in the following experimental examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0020] Example 1 The preparation method of the Fe@C composite material / rubber based on MOFs derivative in this embodiment comprises the following steps: (1) Add 12.2 g of aminoterephthalic acid and 91.4 g of ferric chloride to 250 mL of DMF and stir at 130 r / min for 5 h at 50 °C to generate Fe-MOF; then add 100.0 g of polyacrylonitrile (PAN) and continue stirring at 130 r / min for 5 h, and then stir at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) vacuum carbonizing the jelly-like precursor, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, heating to 230°C at a rate of 2.0°C / min for carbonization for 2 h, then heating to 650°C at a rate of 2.0°C / min for carbonization for 2 h, and naturally cooling to room temperature after carbonization to obtain a Fe@C composite material derived from MOFs; (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Fe@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the open mill was set to a roller gap of 1mm, and 100g of natural rubber was first put in for plasticization for 10 minutes. Then the roller gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roller gap was adjusted back to 1mm, and 0.5g antioxidant, 1g stearic acid, 0.5g zinc oxide, 20g Fe@C composite material, 3g accelerator, and 1g sulfur were added in turn for mixing, and each time the filler was added, the mixing was not less than 5 minutes. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0021] Example 2 The preparation method of the Fe@C composite material / rubber based on MOFs derivative in this embodiment comprises the following steps: (1) Add 24.4 g aminoterephthalic acid and 91.4 g ferric chloride to 250 mL DMF, and stir magnetically at 130 r / min for 5 h at 50 °C to generate Fe-MOF; then add 100.0 g polyacrylonitrile (PAN) and continue to stir magnetically at 130 r / min for 5 h, and then stir at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) vacuum carbonizing the jelly-like precursor, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, heating to 230°C at a rate of 2.0°C / min for carbonization for 2 h, then heating to 650°C at a rate of 2.0°C / min for carbonization for 2 h, and naturally cooling to room temperature after carbonization to obtain a Fe@C composite material derived from MOFs; (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Fe@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the open mill was set to a roller gap of 1mm, and 100g of natural rubber was first put in for plasticization for 10 minutes. Then the roller gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roller gap was adjusted back to 1mm, and 0.5g antioxidant, 1g stearic acid, 0.5g zinc oxide, 20g Fe@C composite material, 3g accelerator, and 1g sulfur were added in turn for mixing, and each time the filler was added, the mixing was not less than 5 minutes. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0022] Example 3 The preparation method of the Fe@C composite material / rubber based on MOFs derivative in this embodiment comprises the following steps: (1) Add 36.6 g aminoterephthalic acid and 91.4 g ferric chloride to 250 mL DMF, and stir magnetically at 130 r / min for 5 h at 50 °C to generate Fe-MOF; then add 100.0 g polyacrylonitrile (PAN) and continue to stir magnetically at 130 r / min for 5 h, and then stir at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) vacuum carbonizing the jelly-like precursor, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, heating to 230°C at a rate of 2.0°C / min for carbonization for 2 h, then heating to 650°C at a rate of 2.0°C / min for carbonization for 2 h, and naturally cooling to room temperature after carbonization to obtain a Fe@C composite material derived from MOFs; (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Fe@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the open mill was set to a roller gap of 1mm, and 100g of natural rubber was first put in for plasticization for 10 minutes. Then the roller gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roller gap was adjusted back to 1mm, and 0.5g antioxidant, 1g stearic acid, 0.5g zinc oxide, 20g Fe@C composite material, 3g accelerator, and 1g sulfur were added in turn for mixing, and each time the filler was added, the mixing was not less than 5 minutes. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0023] Example 4 The preparation method of the Co@C composite material / rubber based on MOFs derivative in this embodiment comprises the following steps: (1) 12.2 g of citric acid and 65.1 g of cobalt nitrate were added to 250 mL of DMF and magnetically stirred at 130 r / min for 2 h at 60 °C to generate Co-MOF; 100.0 g of polyacrylonitrile (PAN) was then added and magnetically stirred at 130 r / min for 2 h, and then stirred at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 350°C at a rate of 5.0°C / min and carbonized for 2 h, and then the temperature is raised to 850°C at a rate of 5°C / min and carbonized for 2 h. After the carbonization, it is naturally cooled to room temperature to obtain a MOFs-derived Co@C composite material.
[0024] (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Co@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the open mill was set to a roller gap of 1mm, and 100g of natural rubber was first put in for plasticization for 10 minutes. Then the roller gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roller gap was adjusted back to 1mm, and 1.5g antioxidant, 3g stearic acid, 1.5g zinc oxide, 60g Co@C composite material, 6g accelerator, and 3g sulfur were added in turn for mixing, and each time the filler was added, the mixing was not less than 5 minutes. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0025] Example 5 The preparation method of the Co@C composite material / rubber based on MOFs derivative in this embodiment comprises the following steps: (1) Add 24.4 g of citric acid and 65.1 g of cobalt nitrate to 250 mL of DMF and stir at 130 r / min for 2 h at 60 °C to generate Co-MOF; then add 100.0 g of polyacrylonitrile (PAN) and continue stirring at 130 r / min for 2 h, and then stir at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 350°C at a rate of 5.0°C / min and carbonized for 2 h, and then the temperature is raised to 850°C at a rate of 5°C / min and carbonized for 2 h. After the carbonization, it is naturally cooled to room temperature to obtain a MOFs-derived Co@C composite material.
[0026] (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Co@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the open mill was set to a roller gap of 1mm, and 100g of natural rubber was first put in for plasticization for 10 minutes. Then the roller gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roller gap was adjusted back to 1mm, and 1.5g antioxidant, 3g stearic acid, 1.5g zinc oxide, 60g Co@C composite material, 6g accelerator, and 3g sulfur were added in turn for mixing, and each time the filler was added, the mixing was not less than 5 minutes. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0027] Example 6 The preparation method of the Co@C composite material / rubber based on MOFs derivative in this embodiment comprises the following steps: (1) 36.6 g of citric acid and 65.1 g of cobalt nitrate were added to 250 mL of DMF and magnetically stirred at 130 r / min for 2 h at 60 °C to generate Co-MOF; 100.0 g of polyacrylonitrile (PAN) was then added and magnetically stirred at 130 r / min for 2 h, and then stirred at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 350°C at a rate of 5.0°C / min and carbonized for 2 h, and then the temperature is raised to 850°C at a rate of 5°C / min and carbonized for 2 h. After the carbonization, it is naturally cooled to room temperature to obtain a MOFs-derived Co@C composite material.
[0028] (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Co@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the open mill was set to a roller gap of 1mm, and 100g of natural rubber was first put in for plasticization for 10 minutes. Then the roller gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roller gap was adjusted back to 1mm, and 1.5g antioxidant, 3g stearic acid, 1.5g zinc oxide, 60g Co@C composite material, 6g accelerator, and 3g sulfur were added in turn for mixing, and each time the filler was added, the mixing was not less than 5 minutes. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0029] Example 7 The preparation method of the MOFs-derived Ni@C composite material / rubber in this embodiment comprises the following steps: (1) 12.2 g of dipyridine carboxylic acid and 65.1 g of nickel acetylacetonate were added to 250 mL of DMF and magnetically stirred at 130 r / min for 2 h at 60 °C to generate Ni-MOF; 100.0 g of polyacrylonitrile (PAN) was then added and magnetically stirred at 130 r / min for 2 h, and then stirred at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 300°C at a rate of 2.5°C / min and carbonized for 1 h, and then the temperature is raised to 750°C at a rate of 2.5°C / min and carbonized for 1 h. After the carbonization, it is naturally cooled to room temperature to obtain a MOFs-derived Ni@C composite material.
[0030] (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Ni@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the open mill was set to a roller gap of 1mm, and 100g of natural rubber was first put in for plasticization for 10min. Then the roller gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roller gap was adjusted back to 1mm, and 1g antioxidant, 2g stearic acid, 1.5g zinc oxide, 40g Ni@C composite material, 6g accelerator, and 3g sulfur were added in turn for mixing, and each time the filler was added, the mixing was not less than 5min. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0031] Example 8 The preparation method of the MOFs-derived Ni@C composite material / rubber in this embodiment comprises the following steps: (1) 24.4 g of pyridine dicarboxylic acid and 65.1 g of nickel acetylacetonate were added to 250 mL of DMF and magnetically stirred at 130 r / min for 2 h at 60 °C to generate Ni-MOF; 100.0 g of polyacrylonitrile (PAN) was then added and magnetically stirred at 130 r / min for 2 h, and then stirred at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 300°C at a rate of 2.5°C / min and carbonized for 1 h, and then the temperature is raised to 750°C at a rate of 2.5°C / min and carbonized for 1 h. After the carbonization, it is naturally cooled to room temperature to obtain a MOFs-derived Ni@C composite material.
[0032] (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Ni@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the roll gap of the open mill was set to 1mm, and 100g of natural rubber was first put in for plasticization for 10min. Then the roll gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roll gap was adjusted back to 1mm, and 1.5g antioxidant, 3g stearic acid, 1g zinc oxide, 35g Ni@C composite material, 6g accelerator, and 3g sulfur were added in turn for mixing, and each time the filler was added, the mixing was not less than 5min. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0033] Example 9 The preparation method of the MOFs-derived Ni@C composite material / rubber in this embodiment comprises the following steps: (1) 36.6 g of pyridine dicarboxylic acid and 65.1 g of nickel acetylacetonate were added to 250 mL of DMF and magnetically stirred at 130 r / min for 2 h at 60 °C to generate Ni-MOF; 100.0 g of polyacrylonitrile (PAN) was then added and magnetically stirred at 130 r / min for 2 h, and then stirred at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 300°C at a rate of 2.5°C / min and carbonized for 1 h, and then the temperature is raised to 750°C at a rate of 2.5°C / min and carbonized for 1 h. After the carbonization, it is naturally cooled to room temperature to obtain a MOFs-derived Ni@C composite material.
[0034] (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Ni@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the roll gap of the open mill was set to 1mm, and 100g of natural rubber was first put in for plasticization for 10 minutes. Then the roll gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roll gap was adjusted back to 1mm, and 0.5g antioxidant, 1g stearic acid, 0.5g zinc oxide, 30g Ni@C composite material, 5g accelerator, and 2g sulfur were added in turn for mixing. Each time the filler was added, the mixing was not less than 5 minutes. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0035] Example 10 The preparation method of the FeCoNi@C composite material / rubber based on MOFs in this embodiment comprises the following steps: (1) 12.2 g of terephthalic acid (PA), 30.5 g of ferric acetylacetonate, 21.7 g of cobalt acetylacetonate and 21.9 g of nickel acetylacetonate were added to 250 mL of DMF and magnetically stirred at 130 r / min for 2 h at 60 °C to generate Fe-MOF; 100.0 g of polyacrylonitrile (PAN) was then added and magnetically stirred at 130 r / min for 2 h, and then stirred at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 300°C at a rate of 2.5°C / min and carbonized for 1 h, and then the temperature is raised to 750°C at a rate of 2.5°C / min and carbonized for 1 h. After the carbonization, it is naturally cooled to room temperature to obtain a FeCoNi@C composite material derived from MOFs.
[0036] (3) The MOFs-derived FeCoNi@C composite material and the di-pentane vulcanizer were prepared into a MOFs-derived FeCoNi@C / silicone rubber dual-functional patch for wave absorption and thermal conductivity through rubber mixing and vulcanization. Specifically, 100g of silica gel was mixed with 35g of MOF-derived FoCoNi@C, 50g of spherical Al2O3 (to increase thermal conductivity) and 2g of di-pentane vulcanizer in sequence, and the mixing time of each filler was more than 10 minutes. The mixed rubber was placed in a preheated 14 mm×12 mm×2 mm rubber mold and vulcanized in a plate vulcanizer at 10 MPa and 160°C for 15 minutes.
[0037] Embodiment 11 The preparation method of the FeCoNi@C composite material / rubber based on MOFs in this embodiment comprises the following steps: (1) 24.4 g of terephthalic acid (PA), 30.5 g of ferric acetylacetonate, 21.7 g of cobalt acetylacetonate and 21.9 g of nickel acetylacetonate were added to 250 mL of DMF and magnetically stirred at 130 r / min for 2 h at 60 °C to generate Fe-MOF; 100.0 g of polyacrylonitrile (PAN) was then added and magnetically stirred at 130 r / min for 2 h, and then stirred at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 300°C at a rate of 2.5°C / min and carbonized for 1 h, and then the temperature is raised to 750°C at a rate of 2.5°C / min and carbonized for 1 h. After the carbonization, it is naturally cooled to room temperature to obtain a FeCoNi@C composite material derived from MOFs.
[0038] (3) The MOFs-derived FeCoNi@C composite material, dipentadienyl vulcanizer, and rubber were mixed and vulcanized to form a MOFs-derived FeCoNi@C / silicone rubber dual-functional patch for wave absorption and thermal conductivity. Specifically, 100g of silica gel was mixed with 35g of MOF-derived FoCoNi@C, 50g of spherical Al2O3, and 2g of dipentadienyl vulcanizer in sequence, and the mixing time of each filler was more than 10 minutes. The mixed rubber was placed in a preheated 14 mm×12 mm×2 mm rubber mold and vulcanized in a plate vulcanizer at 10 MPa and 160°C for 15 minutes.
[0039] Example 12 The preparation method of the FeCoNi@C composite material / rubber based on MOFs in this embodiment comprises the following steps: (1) 36.6 g of terephthalic acid (PA), 30.5 g of ferric acetylacetonate, 21.7 g of cobalt acetylacetonate and 21.9 g of nickel acetylacetonate were added to 250 mL of DMF and magnetically stirred at 130 r / min for 2 h at 60 °C to generate Fe-MOF; 100.0 g of polyacrylonitrile (PAN) was then added and magnetically stirred at 130 r / min for 2 h, and then stirred at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 300°C at a rate of 2.5°C / min and carbonized for 1 h, and then the temperature is raised to 750°C at a rate of 2.5°C / min and carbonized for 1 h. After the carbonization, it is naturally cooled to room temperature to obtain a FeCoNi@C composite material derived from MOFs.
[0040] (3) The MOFs-derived FeCoNi@C composite material, dipentadienyl vulcanizer, and rubber were mixed and vulcanized to form a MOFs-derived FeCoNi@C / silicone rubber dual-functional patch for wave absorption and thermal conductivity. Specifically, 100g of silica gel was mixed with 35g of MOF-derived FoCoNi@C, 50g of spherical Al2O3, and 2g of dipentadienyl vulcanizer in sequence, and the mixing time of each filler was more than 10 minutes. The mixed rubber was placed in a preheated 14 mm×12 mm×2 mm rubber mold and vulcanized in a plate vulcanizer at 10 MPa and 160°C for 15 minutes.
[0041] Comparative Example 1 This comparative example provides a MOF-derived Fe@C / rubber patch. The preparation method thereof is similar to that of Example 1, except that aminoterephthalic acid is not contained in step (1). The steps are as follows: (1) Add 91.4 g of ferric chloride to 250 mL of DMF and stir magnetically at 130 r / min for 2 h at 60 °C to generate Fe-MOF; then add 100.0 g of polyacrylonitrile (PAN) and continue stirring magnetically at 130 r / min for 2 h, and then stir at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) vacuum carbonizing the jelly-like precursor, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, heating to 300°C at a rate of 2.5°C / min for carbonization for 1 h, then heating to 750°C at a rate of 2.5°C / min for carbonization for 1 h, and naturally cooling to room temperature after carbonization to obtain a Fe@C composite material derived from MOFs; (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Fe@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the roll gap of the open mill was set to 1mm, and 100g of natural rubber was first put in for plasticization for 10min. Then the roll gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roll gap was adjusted back to 1mm, and 1.5g of antioxidant, 3g of stearic acid, 1.5g of zinc oxide, 60g of Co@C composite material, 6g of accelerator, and 3g of sulfur were added in turn for mixing. Each time the filler was added, the mixing was not less than 5min. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0042] Comparative Example 2 This comparative example provides a MOF-derived Co@C / rubber patch. The preparation method thereof is similar to that of Example 4, except that citric acid is not contained in step (1). The preparation steps are as follows: (1) Add 65.1 g of cobalt nitrate to 250 mL of DMF and stir at 130 r / min for 2 h at 60 °C to generate Co-MOF; then add 100.0 g of polyacrylonitrile (PAN) and continue stirring at 130 r / min for 2 h, and then stir at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 350°C at a rate of 5.0°C / min and carbonized for 2 h, and then the temperature is raised to 850°C at a rate of 5°C / min and carbonized for 2 h. After the carbonization, it is naturally cooled to room temperature to obtain a MOFs-derived Co@C composite material.
[0043] (3) Raw rubber (natural rubber), additives (anti-aging agent, stearic acid, zinc oxide, accelerator and sulfur), and MOFs-derived Co@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the open mill was set to a roller gap of 1mm, and 100g of natural rubber was first put in for plasticization for 10 minutes. Then the roller gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roller gap was adjusted back to 1mm, and 1.5g antioxidant, 3g stearic acid, 1.5g zinc oxide, 60g Co@C composite material, 6g accelerator, and 3g sulfur were added in turn for mixing, and each time the filler was added, the mixing was not less than 5 minutes. Spray the preheated 180mm×180mm×2mm rubber mold with release agent, put in the refined rubber sheet, and put the mold into the flat vulcanizer for vulcanization. Set the vulcanization pressure to 10MPa, the vulcanization temperature to 150℃, and the vulcanization time to 20min.
[0044] Comparative Example 3 This comparative example provides a MOF-derived Ni@C / rubber patch. The preparation method thereof is as described in Example 7, except that step (1) does not contain dipyridine carboxylic acid. The preparation steps are as follows: (1) Add 65.1 g of nickel acetylacetonate to 250 mL of DMF and stir at 130 r / min for 2 h at 60 °C to generate Ni-MOF; then add 100.0 g of polyacrylonitrile (PAN) and continue stirring at 130 r / min for 2 h, and then stir at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 300°C at a rate of 2.5°C / min and carbonized for 1 h, and then the temperature is raised to 750°C at a rate of 2.5°C / min and carbonized for 1 h. After the carbonization, it is naturally cooled to room temperature to obtain a MOFs-derived Ni@C composite material.
[0045] (3) Raw rubber, additives, and MOFs-derived Ni@C composite materials were prepared into MOFs-derived metal@carbon / rubber wave absorbing and thermal conductive dual-function patches through rubber mixing and vulcanization processes. Specifically, the roll gap of the open mill was set to 1mm, and 100g of natural rubber was first put in for plasticization for 10min. Then the roll gap was adjusted to 0.5mm, and 10 thin passes were performed. After the end, the roll gap was adjusted back to 1mm, and 1g antioxidant, 2g stearic acid, 1g zinc oxide, 35g Ni@C composite material, 5g accelerator, and 2g sulfur were added in sequence for mixing. Each time the filler was added, the mixing time was not less than 5min. The preheated 180mm×180mm×2mm rubber mold was sprayed with a release agent, and the refined rubber was put in. The mold was placed in a flat vulcanizer for vulcanization, and the vulcanization pressure was set to 10MPa, the vulcanization temperature was 150℃, and the vulcanization time was 20min.
[0046] Comparative Example 4 This comparative example provides a MOF-derived FeCoNi@C / rubber patch. The preparation method thereof is similar to that of Example 10, except that PA is not contained in step (1). The preparation steps are as follows: (1) 30.5 g of ferric acetylacetonate, 21.7 g of cobalt acetylacetonate and 21.9 g of nickel acetylacetonate were added to 250 mL of DMF and magnetically stirred at 130 r / min for 2 h at 60 °C to generate Fe-MOF; 100.0 g of polyacrylonitrile (PAN) was then added and magnetically stirred at 130 r / min for 2 h, and then stirred at 130 r / min for 12 h at room temperature to obtain a jelly-like precursor; (2) The jelly-like precursor is vacuum carbonized, specifically: in a nitrogen atmosphere and a vacuum degree of 3 Pa, the temperature is raised to 300°C at a rate of 2.5°C / min and carbonized for 1 h, and then the temperature is raised to 750°C at a rate of 2.5°C / min and carbonized for 1 h. After the carbonization, it is naturally cooled to room temperature to obtain a FeCoNi@C composite material derived from MOFs.
[0047] (3) The MOFs-derived FeCoNi@C composite material and the di-pentane vulcanizer were prepared into a MOFs-derived FeCoNi@C / silicone rubber wave absorbing and thermal conductive dual-function patch through rubber mixing and vulcanization. Specifically, 100g of silicone rubber was mixed with 35g of MOF-derived FoCoNi@C, 50g of spherical Al2O3 and 2g of di-pentane vulcanizer in sequence, and the mixing time of each filler was more than 10 minutes. The mixed rubber was placed in a preheated 14 mm×12 mm×2 mm rubber mold and vulcanized in a plate vulcanizer at 10 MPa and 160°C for 15 minutes.
[0048] Analysis of implementation effect examples 1. The Fe@C composite materials of Example 2 and Comparative Example 1 were characterized by transmission electron microscopy and energy spectrum. The results are as follows: Figure 1 As shown; Figure 1 ab show the TEM images of Fe@C of Comparative Example 1 and MOF-derived Fe@C of Example 2, respectively. It can be seen that in Comparative Example 1, a large number of Fe metal particles of different particle sizes are sparsely dispersed in Fe@C, because a large number of Fe metal particles undergo a large amount of agglomeration during the carbon thermal reduction process. Excessively large metal particles are difficult to display in a transmission electron microscope. In contrast, the metal particles in the MOF-derived Fe@C sample are more densely distributed and have a uniform particle size. This shows that the introduction of the MOF structure effectively inhibits the agglomeration of magnetic nanoparticles, and the refinement of magnetic nanoparticles helps to improve the Snoek limit of the absorber. In addition, the porous structure of the material and the uniformly dispersed magnetic nanoparticles can also increase the interface polarization loss and improve impedance matching. Figure 1 (cf) shows the HAADF-STEM and EDX mapping images of the MOF-derived Fe@C composite. It can be seen that the C and O elements are evenly distributed, and the Fe nanoparticles of similar size are small, dense, monodispersed and randomly distributed in the carbon matrix.
[0049] 2. The Co@C composite materials of Example 5 and Comparative Example 2 were characterized by XRD. The results are as follows: Figure 2 The Ni@C composite materials of Example 8 and Comparative Example 3 were characterized by XRD. Figure 2 b; The FeCoNi@C composite materials of Example 11 and Comparative Example 4 were characterized by XRD, and the results were as follows Figure 2 As shown in c.
[0050] Depend on Figure 2a It can be seen that the peaks at 44.6°, 51.7° and 76.5° originate from the (111), (200) and (220) crystal planes of Co, respectively (PDF#15-0806). It can be found that after the introduction of the MOF structure, the diffraction peak of metallic cobalt becomes sharp and intense, which indicates that the MOF structure is not only beneficial to the refinement of metal nanoparticles, but also to the crystallization of metal nanoparticles. The diffraction peak at 25.1° originates from the (002) crystal plane of graphite (PDF#41-1487). The graphite diffraction peak is generated by the catalysis of Co during the carbonization process of PAN. It can be seen that the introduction of the MOF structure is also beneficial to the formation of graphite.
[0051] Depend on Figure 2 b It can be seen that the characteristic diffraction peaks at 44.5°, 51.9° and 76.4° correspond to the (111), (200) and (220) crystal planes of face-centered cubic Ni, respectively (PDF#04-0850); the diffraction peaks at 37.3°, 43.4° and 62.9° correspond to the (111), (200) and (220) crystal planes of NiO, respectively (PDF#47-1049); the appearance of the graphite diffraction peak is due to the catalytic effect of Ni in the carbonization process of PAN. In addition, by comparing the XRD curves, it can be found that in the curve of comparative example 3, the graphite peak is almost a steamed bun peak, the characteristic peak of NiO is relatively strong, and the characteristic peak of Ni is relatively weak. After the introduction of the MOF structure, the graphite peak becomes sharper, the characteristic peak of NiO weakens with the increase of the amount of pyridine dicarboxylic acid added until it almost disappears, and the characteristic peak of Ni is enhanced. This shows that the addition of pyridine dicarboxylic acid can promote Ni 2+ The carbothermal reduction process and the formation of graphite in carbon materials.
[0052] Figure 2 c shows the XRD spectra of FoCoNi@C (Comparative Example 4) and MOF-derived FoCoNi@C (Example 11). The peak at 25.6° belongs to the (002) crystal plane of graphite. The peaks at 44.2°, 51.6° and 75.7° correspond to the (111), (200) and (220) planes of the face-centered cubic of the FoCoNi alloy, respectively, indicating that the metal salt is reduced to FeCoNi alloy during the carbon thermal reduction process. Similar to the previous case, the sample with the introduction of the MOF structure exhibited sharper FoCoNi alloy diffraction peaks and stronger graphite diffraction peaks. The above results show that the MOF structure has a significant effect on the confinement effect of metal particles, improving metal crystallinity and enhancing the degree of graphitization of carbon materials during the carbon thermal reduction process, and is universal.
[0053] 3. Wave absorption performance test: The Fe@C / silicone rubber of Example 2 and Comparative Example 1 were cut into concentric rings with an outer diameter of 7 mm and an inner diameter of 3.04 mm, and the wave absorbing performance was tested.
[0054] (1) According to the transmission line theory, the reflection loss (RL) of the composite absorber is calculated. The curve of RL changing with frequency is as follows: Figure 3 As shown in ab, Figure 3 cd is the corresponding interference destructive curve.
[0055] Depend on Figure 3 From ab, it can be seen that the RL of most areas of the comparative example 1 in the test range of 2-18GHz is less than -10dB, and only in the high-frequency area with a thickness of 5.0mm, the minimum RL reaches -24.9dB; for Example 2, at a thickness of 5.0mm and a frequency of 13.6GHz, the minimum RL reaches -31.9dB (Figure d). It can be found that the RL value and the effective absorption bandwidth show an increasing trend with the increase of the aminoterephthalic acid content. In addition, from Figure 3 It can be seen that the curves of Comparative Example 1 and Example 2 obey the λ / 4 model over the entire measurement frequency, which is conducive to electromagnetic wave interference destructiveness.
[0056] 4. Thermal conductivity test: Electronic components will inevitably generate a lot of waste heat during operation, and absorbent materials with high thermal conductivity can help dissipate excess heat to meet thermal conductivity. Figure 4 The surface temperature of pure silicone rubber, comparative example 4 and example 11 samples changes with heating time. The surface temperature of the samples within 120 seconds of heating was calculated starting from 28°C. Obviously, the thermal conductivity of silicone rubber is significantly improved with the addition of terephthalic acid. This shows that the introduction of MOF structure is conducive to the enhancement of thermal conductivity of the absorber.
[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing metal@carbon / rubber based on MOFs, characterized in that: The steps are: (1) dissolving a bis-acid derivative, a metal salt and polyacrylonitrile in a solvent, and sequentially performing a heating reaction and a room temperature reaction to obtain a jelly-like precursor solution; (2) The precursor solution of step (1) is carbonized at high temperature to obtain a metal@carbon composite material derived from MOFs; (3) The rubber, the additive and the MOFs-derived metal@carbon composite material of step (2) are prepared into MOFs-derived metal@carbon / rubber through rubber kneading and vulcanization processes.
2. The method for preparing metal@carbon / rubber based on MOFs according to claim 1, characterized in that: In the step (1), the bis-acid derivative is any one of aminoterephthalic acid, terephthalic acid, pyridine dicarboxylic acid and citric acid; and the metal salt is one or more of iron salt, nickel salt and cobalt salt.
3. The method for preparing metal@carbon / rubber based on MOFs according to claim 2, characterized in that: The iron salt is any one of ferric acetylacetonate, ferric nitrate, ferric chloride and ferric sulfate; the nickel salt is any one of nickel acetylacetonate, nickel nitrate, nickel chloride and nickel sulfate; the cobalt salt is any one of cobalt acetylacetonate, cobalt nitrate, cobalt chloride and cobalt sulfate.
4. The method for preparing metal@carbon / rubber based on MOFs according to any one of claims 1 to 3, characterized in that: The mass ratio of the terephthalic acid derivative, the metal salt and the polyacrylonitrile is 3-9:16-23:16-25.
5. The method for preparing metal@carbon / rubber based on MOFs according to claim 4, characterized in that: The heating reaction temperature in step (1) is 50-70°C for 2-5 hours; the reaction time at room temperature is 12-24 hours.
6. The method for preparing metal@carbon / rubber based on MOFs according to claim 5, characterized in that: In the step (2), the high temperature carbonization adopts staged carbonization. The heating rate of the first stage is 2-5°C / min, the carbonization temperature is 230-350°C, and the time is 1-2h. The heating rate of the second stage is 2-5°C / min, the carbonization temperature is 650-850°C, and the time is 1-2h.
7. The method for preparing metal@carbon / rubber based on MOFs according to claim 6, characterized in that: In step (3), the rubber is natural rubber or silicone rubber; the additives include one or more of an antioxidant, stearic acid, zinc oxide / nano zinc oxide, an accelerator and a vulcanizing agent; wherein the antioxidant is antioxidant D, the accelerator is accelerator CZ, and the vulcanizing agent is sulfur or dipentadienyl vulcanizing agent.
8. The method for preparing metal@carbon / rubber based on MOFs according to claim 7, characterized in that: The mass ratio of the rubber, antioxidant, stearic acid, zinc oxide / nano zinc oxide, accelerator, vulcanizing agent and MOFs-derived metal@carbon composite material is 100:0.5-1.5:1-3:0.5-1.5:4-6:1-3:20-60.
9. Metal@carbon / rubber derived from MOFs prepared by the method described in any one of claims 1-3 and 5-8.
10. Use of the metal@carbon / rubber derived from MOFs as claimed in claim 9 in the preparation of dual-functional materials for wave absorption and thermal conduction.
Citation Information
Patent Citations
Electromagnetic shielding rubber with high thermal conductivity, preparation method and application thereof
CN107236161A
Heat-conducting and wave-absorbing sheet and preparation method thereof
CN113929963A
Metal / carbon nano composite fiber derived based on MOFs (Metal Organic Frameworks) as well as preparation method and application of metal / carbon nano composite fiber
CN114875525A
Low-odor elastomer material and preparation method thereof
CN115449134A
Low-temperature vulcanized rubber material and preparation method thereof
CN115612189A